86.2k views
5 votes
This equation has one solution. 3(x – 2) + 4x = 10(x + 1) What is the solution?

A.) -5
B.) -2
C.) -16/3
D.) -16/7

2 Answers

1 vote

Answer:

Choice C -16/3

Explanation:

3(x – 2) + 4x = 10(x + 1) <-- Distribute

3x - 6 + 4x = 10x + 10 <-- Combine all like terms

7x - 6 = 10x + 10 <-- Combine all like terms in one side

7x - 10x = 10 + 6 <-- Simplify

-3x = 16 <-- Isolate x by dividing

x = -16/3

User Rigobert Song
by
5.4k points
1 vote

Answer:

C) -16/3

Explanation:

3(x – 2) + 4x = 10(x + 1)

Multiply 3x-6+4x=10x+10

Combine like terms 7x-6=10x+10

Subtract 7x from both sides -6=3x+10

Subtract 10 from both sides -16=3x

Divide -16/3=x

User Dave Shinkle
by
5.8k points